Characterization of pTMCnLiPF6 solid polymer electrolytes - Barbosa, P. C. (2011)
In this study the results our characterization of a solid polymer electrolyte based on poly(trimethylene carbonate), henceforth designated as p(TMC), and lithium hexafluorophosphate (LiPF6) are described. Samples of solvent-free electrolytes were prepared with a range of concentration of guest salt using solvent casting from tetrahydrofuran and characterized by conductivity measurements, thermal analysis and electrochemical stability. Electrolytes based on this host polymer, with LiPF6, were obtained as mechanically robust, flexible, transparent and completely amorphous films.